PROCESS AND SYSTEMS Patient Journey Champions: A project to facilitate delivery of effective board rounds for inpatients, aiding flow through the hospital. Issue 3 (2020) - Saqib, Aaisha; Waugh, William; Jayasinghe, Rebecca; Banerjee, Sandip
No abstract available